We'll be using the quotient rule for this one:
d/dx[f(x)/g(x)]=(f'(x)g(x)-g'(x)f(x))/((g(x))^2)
Let:
f(x)=1+ln(3x^2)
g(x)=1+ln(4x)
So:
Use color(blue)(d/dx[ln(u)]=1/u*u'
f'(x)=color(blue)(d/dx[1]+d/dx[ln(3x^2)]=0+1/(3x^2)*d/dx[3x^2]=1/(3x^2)*6x=(6x)/(3x^2)=color(red)(2/x
g'(x)=color(blue)(d/dx[1]+d/dx[ln(4x)]=0+1/(4x)*d/dx[4x]=1/(4x)*4=4/(4x)=color(red)(1/x
By the product rule:
=(2/x*1+ln(4x)-1/x*1+ln(3x^2))/((1+ln(4x))^2)
=((2(1+ln(4x)))/x-((1+ln(3x^2)))/x)/((1+ln(4x))^2
=((2(1+ln(4x))-(1+ln(3x^2)))/x)/((1+ln(4x))^2
Apply the fraction rule for further simplification: (a/b)/c=a/b*1/c
=(2(1+ln(4x))-(1+ln(3x^2)))/x*1/(1+ln(4x))^2
=(2(1+ln(4x))-(1+ln(3x^2)))/(x(1+ln(4x))^2)
We can simplify the numerator if desired
color(blue)(2(1+ln(4x))-(1+ln(3x^2))=2+2ln(4x)-1-ln(3x^2)
Applying several log rules...
color(blue)(2+ln(4x)^2-1-ln(3x^2)
color(blue)(1+ln((4x)^2/(3x^2))=1+ln((16x^2)/(3x^2))=color(red)(1+ln(16/3)
:.d/dx[(1+ln(3x^2))/(1+ln(4x))]=(1+ln(16/3))/(x(1+ln(4x))^2)